Ampliação da capacidade de análise: a produção de sentidos na Política Nacional de Humanização - Garcia Júnior, Carlos Alberto Severo; Pedebôs, Lucas Alexandre; Noguez, Camila; Yasui, Silvio [UNESP] (My University, 2014)
The article refers to the collective construction performed from the Multicentric Research on Humanization Training of SUS. It is about production and building consensus on different interpretations of the superfamily "expansion of the analysis capability." The methodological approach is related to the creation of analytical reports coming from four sources: Intervention Plans built at the time of training courses offered in three states (Rio Grande do Sul, Santa Catarina and São Paulo) by the institutional supporters in training.Also, there were questionnaires answered via Form-SUS by graduated supporters after four years of the course closing; data and analysis produced by supporters in focus groups and interviews, conducted as the research final stage in the three states.Thus, considering the inclusive methodological framework not only from the courses, but also the research that evaluated them, the participants (graduates from the training courses) produced data and started to play the active role of researchers/panelists because they got “surprised" by partial analyzes.Therefore, the article discusses the analysis capability of demand required by supporters before their working areas and the relationship of that capability with concepts and elements of Institutional Analysis.It was possible to highlight the inseparability between demands of emergency and the exercise of being next to another person and his/her interests. The conclusion is that the methodology proposed by the course allowed the supporters in training to stimulate and develop a critical capacity on their work.However, it is noticed that the expansion of such analytical capability often remained linked to the supporter, without the contagion of other workers in the territories.It was also possible to see that the course and political framework of PNH could equip the supporters, promoting empowerment from their analysis, which is essential to the interventions performance.

O presente artigo refere-se à construção coletiva realizada a partir da Pesquisa Multicêntrica sobre Formação em Humanização do SUS. Trata-se de uma produção e construção de consensos sobre as diferentes formas de interpretação da superfamília “ampliação da capacidade de análise”. Tem-se como percurso metodológico a constituição de relatórios analíticos advindos de quatro fontes: Planos de Intervenção construídos à época dos cursos de Formação oferecidos em três estados (Rio Grande do Sul, Santa Catarina e São Paulo) pelos apoiadores institucionais em formação; questionários respondidos via Form-SUS pelos apoiadores já formados após quatro anos de encerramento do curso; dados e análises produzidos pelos apoiadores em grupos focais e entrevistas, realizados como etapa final da pesquisa nos três estados. Assim, considerando o referencial metodológico inclusivo, tanto dos cursos, como da pesquisa que os avaliaram, os participantes da pesquisa (egressos dos referidos cursos de formação) não só produziram os dados, mas passaram a exercer o papel ativo de pesquisadores/debatedores ao “estranharem” as análises parciais. Dessa forma, o artigo abordou a capacidade de análise de demanda exigida dos apoiadores diante de seus territórios de atuação e a relação dessa capacidade com conceitos e elementos da Análise Institucional, sublinhando a indissociabilidade entre emergência das demandas e o exercício de se colocar junto ao outro e seus interesses. Concluiu-se que a metodologia proposta pelo curso permitiu que os apoiadores em formação estimulassem e desenvolvessem uma capacidade crítica sobre o seu fazer; porém, percebeu-se que a ampliação de tal capacidade analítica, muitas vezes, permaneceu adstrita ao apoiador, sem o contágio dos demais trabalhadores nos territórios. Viu-se também que o curso e o marco político da PNH podem instrumentalizar os apoiadores, promovendo o empoderamento, a partir de suas análises, essencial à realização das intervenções.
Extension of the analysis capability: production of meanings in the National Humanization Policy
Keywords: Care Humanization; Health Evaluation; Public Health Policies; Humanização da Assistência; Avaliação em Saúde; Políticas Públicas de Saúde